Outcome Assessment of Steritin Tulle Gauze, Aquacel Ag and Kaltostat Dressing at Skin Graft Donor Sites: Assessment of Steritin Tulle Gauze, Aquacel Ag and Kaltostat - Katpar, Hira; Sara Noor; Rana Hassan Javaid; Bajwa, Ghazanfar Ali; Farah Naz; Abdul Rasool (Pakistan Journal of Health Sciences, 2023)
Split Thickness Skin Graft (STSG) is a common surgical procedure used to reconstruct defects in plastic surgery. Various dressing options are available for the donor site, each with its pros and cons. Objective: To compare the effectiveness of three dressing options for STSG donor sites. Methods: The study was conducted from April to September 2022. Sixty patients were randomized equally into three groups and assessed for wound healing, pain, infection, and ease of dressing removal. The dressing options were Steritin Tulle gauze, Aquacel Ag, and Kaltostat. Results: All donor sites healed within 14-days, and no infections were observed. Aquacel Ag dressing caused less pain in early post-operative days, and Kaltostat dressing was easier to remove compared to Steritin dressing. Conclusions: Our study found that the use of Aquacel Ag and Kaltostat dressing can be more beneficial for Split Thickness Skin Graft donor sites.